Green Silver Nanoparticles Confined in Monolithic Silica Disk-packed Spin Column for Human Serum Albumin Preconcentration - Alzahrani, Eman (Current Analytical Chemistry, 2019)
Background: In recent times many new uses have been found for nanomaterials that have undergone homogenous immobilization within porous supports. For this paper, immobilization of SNPs on a thiol-functionalized silica monolith using a fast, easy, environmentally friendly and costeffective process was performed. This was achieved by modifying the surface of a silica-based monolith using thiol groups, and then we fabricated green SNPs in situ, reducing an inorganic precursor silver nitrate solution (AgNO3) by employing tangerine peel extract as a reducing reagent, with Ag-thiol bonds forming along the monument. Doing this allows monoliths to be prepared in such a way that, as TEM analysis demonstrated, SNPs are evenly distributed along the rod's length. Once the materials had been fabricated, they were employed as a sorbent by being placed in a centrifuge. The SNP-thiol functionalized silica monolith was then tested using a standard protein (HSA). Methods: The process involves creating monolithic materials by employing a two-part sol-gel technique before modifying the surface of the silica-based monolith using thiol groups for hosting purposes. Homogenous surface coverage was achieved through the use of a non-toxic
Keywords: HSA